Glyoxalase 1 expression is associated with an unfavorable prognosis of oropharyngeal squamous cell carcinoma - Kreycy, Nele; Fleming, Thomas; Flechtenmacher, Christa; Grabe, Niels; Plinkert, Peter K.; Heß, Jochen; Plath, Karim (BMC cancer, 2017)
Glyoxalase 1 is a key enzyme in the detoxification of reactive metabolites such as methylglyoxal and induced Glyoxalase 1 expression has been demonstrated for several human malignancies. However, the regulation and clinical relevance of Glyoxalase 1 in the context of head and neck squamous cell carcinoma has not been addressed so far.